DIGITAL LITERACY IS THE BASIS OF MODERN EDUCATION - Nurmuxamedova Dilfuza Irkenovna (Modern American Journals, 2025)
The article analyzes the concept of digital literacy, its place and significance in the modern education system. The introduction of digital technologies into the educational process, methods of developing digital skills in students and their impact on socio-economic development are considered. The recognition of digital literacy as an integral part of modern education justifies its role in educating the younger generation with the ability to think critically, adaptably to new conditions.
Keywords: Digital literacy, modern education, digitalization, information and communication technologies, innovative approach, creative thinking